Model Desa Berbasis Riset di Desa Kesongo Kecamatan Tuntang Kabupaten Semarang Miniatur Penyelenggaraan Pemerintahan di Indonesia: Research-Based Village Model in Kesongo Village, Tuntang District, Semarang Regency: A Miniature of Government Administration in Indonesia - Joko Mulyono; Lazib Ajibta Kurniawan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
In fact, villages are miniature government administrations in the daily lives of the community. Regional development problems are ultimately at the village level, encompassing issues such as citizen skills education, public services, community creativity, and innovation. This article was written to provide a research-based village model concept as a recommendation for a miniature village government administration. This study employs a qualitative descriptive methodology, which aims to comprehensively describe everyday phenomena by providing an accurate summary of the research object. Data collection was conducted through interviews, focus group discussions (FGDs), observation, and documentation studies. The location of this research is in the villages around Rawa Pening in Semarang Regency. The research analysis technique focuses on analyzing, describing, and summarizing qualitative data to gain a deep understanding of a phenomenon or social condition. The model of village and community governance is expected to generate resources, opportunities, knowledge, potential, and skills, thereby determining the future of development in their villages. Community empowerment continues to develop well with the synergy and collaboration of various stakeholders. Village empowerment is implemented in the innovation of the Research-Based Village concept; 1) compiling the history and potential of local village wisdom, 2) encouraging clean government and good governance in village governments, 3) encouraging the implementation of an Integrated Agricultural System, 4) providing support for the development of MSMEs, and 5) providing support for the Development of the Creative Economy and Circular Economy. The research-based village model is recommended for implementation in Central Java Province and Indonesia, taking into account the potential and local wisdom of each village, with the support of the local Regional Government.